Knowledge and Prevalence of Plantar Fasciitis among Nurses of Selected Hospital of Kathmandu, Nepal - Shrestha, Moonu; Shrestha, Chhabikala; KC, Reshma; Shakya, Sheetal (Academia Research Journal, 2024)
An uncomfortable foot ailment called plantar fasciitis is brought on by an inflammation of the plantar fascia. When this band of tissue is overworked or overextended, plantar fasciitis develops. This results in tiny rips in the fascia's fibers, particularly where it connects to the heel bone. This study set out to determine how much the nurses at the Civil Service Hospital in Kathmandu knew about plantar fasciitis and how common it was. At the Civil Service Hospital in Kathmandu, 58 nurses participated in a descriptive cross-sectional research. Data were gathered using a self-administered questionnaire and the windlass test. SPSS version 20 was used to analyze the data, which included frequency and percentage using a descriptive statistical approach. The results showed that majority of respondents (53.4%) of nurses were age group of 18 to 25 years. Maximum respondents (93.1%) had normal BMI, maximum (46.6%) had 1 to 4 years work experience and majority of respondents (74.1%) worn flats during duty hours. Out of 58 respondents (56.9%) had poor knowledge, (29.3%) satisfactory and (13.8%) had good knowledge regarding plantar fasciitis with positive prevalence of windlass test (63.80%) and (36.2%) had negative windlass test. In the present study, it is concluded that majority of the respondents had (56.9%) poor knowledge, (29.3%) satisfactory and (13.8%) had good knowledge regarding plantar fasciitis with positive prevalence of windlass test (63.80%) and (36.2%) had negative windlass test, which means majority have plantar fasciitis.